Avaliação de mecanismos de ação envolvidos na morte celular de Trypanosoma cruzi induzido pelo eupomatenóide-5 - Bidóia, Danielle Lazarin (2012)
Chagas' disease caused by protozoan Trypanosoma cruzi affects approximately 10 million people in Latin America. Currently, the drugs available for the treatment of this infection are very toxic, with several side effects and low efficacy in the chronic phase. Thus, new alternatives for the treatment of this disease become necessary and priority and natural products are promising candidates due to the diversity of their molecular structures. Previous studies from our research group showed activity of eupomatenoid-5, a neolignan isolated from leaves of Piper regnellii var. pallescens, in T. cruzi. Additionally, the results obtained by transmission and scanning electron microscopy demonstrated morphological and ultrastructural alterations suggesting the possibility that differents structures could be targets of eupomatenoid-5. Thus, the purpose of this study was to evaluate same biochemical changes induced by eupomatenoid-5 in all three forms of T. cruzi in attempt to elucidate the mechanisms involved in cell death of this parasite. Our results showed that the trypanocidal action of eupomatenoid-5 induced change in mitochondrial membrane potential and cell membrane integrity; increased formation of mitochondrial superoxide anion; lipid peroxidation; DNA fragmentation; decreased cell volume and formation of autophagic vacuoles. These results suggest that the trypanocidal action of eupomatenoid-5 is closely related with mitochondrial dysfunction followed by an increase of ROS formation. These are key events to induce cell death through different pathway including, apoptosis, necrosis and autophagy.